Paclitaxel induces Stathmin 1 phosphorylation, microtubule stability and apoptosis in acute lymphoblastic leukemia cells. Issue 9 (September 2017) - Machado-Neto, João Agostinho; Rodrigues Alves, Ana Paula Nunes; Fernandes, Jaqueline Cristina; Coelho-Silva, Juan Luiz; Scopim-Ribeiro, Renata; Fenerich, Bruna Alves; da Silva, Fernanda Borges; Scheucher, Priscila Santos; Simões, Belinda Pinto; Rego, Eduardo Magalhães; Traina, Fabiola
Abstract: Acute lymphoblastic leukemia (ALL) is a hematological malignancy characterized by abnormal proliferation and accumulation of lymphoblasts in the hematopoietic system. Stathmin 1 is a proliferation marker for normal lymphocytes, which has been described as highly expressed in ALL patients and functionally important for leukemia phenotype. In the present study, we expand our previous observations and aim to investigate Stathmin 1 expression and its impact on laboratory features and clinical outcomes in an independent cohort of ALL patients, and to verify the effects of paclitaxel treatment on Stathmin 1 phosphorylation and cell viability in ALL cell lines. In ALL patients, Stathmin 1 expression was significantly increased, associated with lower age onset and positively correlated with white blood cell counts, but did not impact on clinical outcomes. Functional assays revealed that paclitaxel induces Stathmin 1 phosphorylation at serine 16 (an inhibitory site), microtubule stability and apoptosis in Jurkat and Namalwa cell lines. Paclitaxel treatment did not modulate cell viability of normal peripheral blood leukocytes. In conclusion, our data confirm increased levels of Stathmin 1 in ALL patients and that therapeutic doses of paclitaxel inhibits Stathmin 1 function and promote microtubule stability and apoptosis in ALL cells.